Semiotic landscapes : language, image, space - Jaworski, Adam, 1957-; Thurlow, Crispin (Advances in sociolinguistics., 2010)
Semiotic Landscapes is an exciting addition to the study of linguistic landscapes. It looks at how landscape generates meaning and combines three major areas of scholarly interest each concerned with central dimensions of contemporary life: language and visual discourse, spatial practices, and also the changes bought about by global capitalism and ever increasing mediatization. The editors look at: the textual/discursive construction of place; the use of space as a semiotic resource; the extent to which these processes are shaped by wider economic and political re-orderings of post-industrial.